Effect of dietary pomegranate by-product on lamb flavour. (April 2023) - Natalello, Antonio; Menci, Ruggero; Luciano, Giuseppe; Monahan, Frank; Gravador, Rufielyn S.; Valenti, Bernardo; Pauselli, Mariano; Belvedere, Gianni; Scerra, Manuel; Priolo, Alessandro
Abstract: This study evaluated the effect of the dietary inclusion of whole pomegranate by-product (WPB) on lamb flavour. Seventeen Comisana male lambs (body weight 14.82 kg ± 2 kg) were assigned to 2 treatments. During 36-day feeding trial, the control group ( n = 8) received a conventional concentrate diet; the other group ( n = 9) received a concentrate diet containing 200 g/kg (dry matter) of WPB, replacing part of barley and corn. After slaughter, fatty acids were determined in raw meat, while volatile organic compounds, SMart nose, and sensory traits were analysed in cooked meat. The concentrations of total polyunsaturated fatty acids, vaccenic and rumenic acid were higher in WPB meat. Most of volatile compounds that arise from lipid degradation (i.e., aldehydes, alcohols, ketones, and hydrocarbons) were found at higher concentrations in the WPB meat than in the control, except for 2-pentanone that was greater in control meat. Although SMart nose clearly discriminated between dietary treatments, consumer panel did not detect differences in meat flavour.